Word Reading Fluency: Role of Genome‐Wide Single‐Nucleotide Polymorphisms in Developmental Stability and Correlations With Print Exposure. Issue 3 (6th January 2014) - Harlaar, Nicole; Trzaskowski, Maciej; Dale, Philip S.; Plomin, Robert
Abstract : The genetic effects on individual differences in reading development were examined using genome‐wide complex trait analysis (GCTA) in a twin sample. In unrelated individuals (one twin per pair, n  =   2, 942), the GCTA‐based heritability of reading fluency was ~20%–29% at ages 7 and 12. GCTA bivariate results showed that the phenotypic stability of reading fluency from 7 to 12 years ( r  =   0.69) is largely driven by genetic stability (genetic r  =   0.69). Genetic effects on print exposure at age 12 were moderate (~26%) and correlated with those influencing reading fluency at 12 (genetic r  = 0.89), indicative of a gene–environment correlation. These findings were largely consistent with quantitative genetic twin analyses that used both twins in each pair ( n  =   1, 066–1, 409).